PELAKSANAAN PROGRAM USAHA EKONOMI KELURAHAN SIMPAN PINJAM (UEK-SP) DI KELURAHAN SIDOMULYO BARAT KECAMATAN TAMPAN KOTA PEKANBARU - Arlisa, Omi; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The real shape of this program is to serve the small business community who wants to get a loan from the Village Office in the city of Pekanbaru. One of them in Business Economy Village Savings and Loans (UEK-SP) Sidomulyo which is an alternative non-bank financial institutions that can give attention to the poor or the weak economy that wants capital relief effort. The phenomena that occur are the absence of awareness of customers / users and the low quality of human resources. The purpose of this study is to see how the implementation of the Economic Business Programs Village Savings and Loans (UEK-SP) in the Village of West Sidomulyo Pekanbaru City Subdistrict Handsome and determine the factors that influence the implementation of the Economic Business Programs village Savings and Loans (UEK-SP) in the Village Sidomulyo Handsome Western District of the city of Pekanbaru. Nakamura and Smallwood (in Sujianto 2008: 152) argues that there are three dominant way to determine the success of the program that can be seen from compliance, routine procedures and the achievement of program objectives. This research is a qualitative descriptive study, which the authors describe how the implementation of the program Economic Business Village Savings and Loans (UEK-SP) in the Village of West Sidomulyo the District Charming Pekanbaru City by taking the research location that UEK-SP Sidomulyo. Data collection techniques are interviews and the key informant is Chairman UEK-SP Sidomulyo. This study uses snowball sampling to determine informants to be interviewed. Results of this study concluded that the program of economic Esaha Village Savings and Loans (UEK-SP) in the Village of West Sidomulyo Handsome District of the city of Pekanbaru by looking at the indicators that I use, namely compliance, routine procedures and the achievement of the objectives of the program "Less Good". In this study, also known factors that affect the implementation of the Economic Business Programs Village Savings and Loans (UEK-SP) in the village of West Sidomulyo Kecamatan Handsome Pekanbaru namely: Low Human Resources, lack of experience and lack of public awareness. Keywords: Implementation of the program, compliance, routine procedures and the achievement of program objectives